OPTIMALISASI HANDPHONE UNTUK MONITORING RUANGAN MENGGUNAKAN WEBCAM SEBAGAI PENINGKATAN KINERJA KARYAWAN PADA KANTOR KELURAHAN KARANG MEKAR KECAMATAN BANJARMASIN TIMUR - Chandra Anugerah Putra; Nina Widyawati; M.S. Sailillah (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2014)
Monitoring the location of the current space is needed as one of the security or surveillance which can be used for state information on the location of the room. No matter if we are at the location, but if we are not on the site, of course we can not see or monitor room / where we left off. The lack of oversight / monitoring done if leaders are not in an office, employees often abuse that opportunity to other interests, such as out of the office during working hours, lunch break over the time limit is set, perform activities outside duties and functions as an employee, and behaviors of others. It is most likely to solve it is by monitoring the room (streaming webcam) using HP / SmartPhone, with the help of the PC, Modem, Network Internet, and Mobile devices themselves.Keywords: Mobile, Monitoring Room, Webcam, Performance Improvement.